Stress corrosion cracking behavior of austenitic stainless steels in natrium chloride solutions - Elsariti, Samir Milad (School of Mechatronic Engineering, 2013)
The main objective of this research is to identify Stress Corrosion Cracking of austenitic stainless steels in natrium chloride solutions at room temperature.